Insights from remarkable businesspeople - Abrashoff, D. Michael; Wiersema, Frederik D.; Hirshberg, Gary; Kao, John J.; Golden, Michael F.; LeBaron, Dean; Koehn, Nancy F. 1959-; Champy, James 1942-; Mangurian, Glenn E.; Fuller, Edwin D. 1945- (FTPress Delivers, 2011)
"What it takes to lead your team to greatness! Outstanding leaders tell you how to identify and fix even the biggest problems ... get buy-in that's real ... balance external customers and internal processes ... infuse creativity throughout your organization, and reinvent its future ... get results, not salutes!"--Resource description page.
Includes bibliographical references. - Resource description page (viewed Sept. 22, 2010)
Keywords: Success in business; Businesspeople -- United States; Succès dans les affaires; Gens d'affaires; États-Unis; Businesspeople; United States